The effect of the emkontan model on students’ creative thinking skills in environmental pollution topics - Iwan Ridwan Yusup; Nuranisa Dina Amalia; Epa Paujiah (Universitas Negeri Jakarta, 2026)
Creative thinking skills are a crucial component of 21st-century competencies, particularly in issue-based learning such as environmental pollution. This study aimed to examine the effectiveness of the EMKONTAN learning model in enhancing students’ creative thinking skills regarding environmental pollution. A quasi-experimental design with a non-equivalent control group was employed. The participants were seventh-grade students from a junior high school in Bandung, Indonesia. The sample consisted of two classes, with 27 students in the experimental group and 27 students in the control group. The instruments used in this study included several data collection tools, namely observation sheets used to assess students’ creative thinking skills during learning activities, written achievement tests used to measure students’ understanding of environmental pollution concepts, and student questionnaires used to collect information regarding students’ responses to the implementation of the EMKONTAN learning model. Data were analyzed using the Mann-Whitney test, revealing a significant difference between the experimental and control groups (p = 0.047 < 0.05). The normalized gain (N-Gain) score of 0.78 indicated a high level of improvement, with the originality indicator showing the greatest gain and fluency the lowest. The EMKONTAN model, grounded in real-life contexts, effectively facilitated the connection between learning and the students’ environment, promoting meaningful and creative ideas. These findings suggest that the EMKONTAN model is a practical and effective approach for environmentally-themed learning to enhance students’ creative thinking skills.